Pengaruh Motivasi Belajar dan Persepsi Siswa atas Kemampuan Pedagogik Guru Terhadap Prestasi Belajar Pendidikan Pancasila dan Kewarganegaraan - Heru Sriyono (Universitas Indraprasta PGRI, 2017)
ABSTRACT The purpose of this study is to determine 1) The influence of learning motivation and perceptions of teacher pedagogic ability together to achievement learn. 2) The influence of learning motivation on student achievement 3) The influence of perception on teacher pedagogic ability to student achievement. The survey method with the technique of inferential statistical analysis of simple correlation and double correlation, and simple regression and multiple regression. Population in this research is the students of class X Private Nurussaadah, MA Private Al-Khairiyah, and MA Private Nurul Amanah 80 South Jakarta. The sample was graduated 80 students of class XI taken by random sampling technique. The results concluded (1) There is a significant influence of learning motivation and perceptions on teacher pedagogic ability together on learning achievement of Pancasila Education and Citizenship of Private Madrasah Aliyah students in South Jakarta; (2) There is a significant influence of learning motivation on learning achievement of Pancasila Education and Citizenship of Private Madrasah Aliyah students in South Jakarta. (3) There is a significant influence of perceptions on teacher pedagogic ability and learning achievement of Pancasila and Citizenship Education, Private Madrasah Aliyah students in South JakartaKeywords: learning motivation, Pedagogic ability, learning achievement ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui 1) Pengaruh motivasi belajar dan persepsi atas kemampuan pedagogik guru secara bersama-sama terhadap prestasi belajar. 2) Pengaruh motivasi belajar terhadap prestasi belajar siswa 3) Pengaruh persepsi atas kemampuan pedagogik guru terhadap prestasi belajar siswa. Metode survei dengan teknik analisis data statistik inferensial korelasi sederhana dan korelasi ganda, serta regresi sederhana dan regresi ganda.Populasi dalam penelitian ini adalah siswa kelas X Swasta Nurussaadah, MA Swasta Al-Khairiyah, dan MA Swasta Nurul Amanah 80 Jakarta Selatan. Sampel berjuamlah 80 siswa kelas XI diambil dengan teknik random sampling. Hasil penelitian menyimpulkan (1) Terdapat pengaruh yang signifikan motivasi belajar dan persepsi atas kemampuan pedagogik guru secara bersama-sama terhadap prestasi belajar Pendidikan Pancasila dan Kewarganegaraan siswa Madrasah Aliyah Swasta di Jakarta Selatan; (2) Terdapat pengaruh yang signifikan motivasi belajar terhadap prestasi belajar Pendidikan Pancasila dan Kewarganegaraan siswa Madrasah Aliyah Swasta di Jakarta Selatan. (3) Terdapat pengaruh yang signifikan persepsi atas kemampuan pedagogik guru dan prestasi belajar Pendidikan Pancasila dan Kewarganegaraan, siswa Madrasah Aliyah Swasta di Jakarta SelatanKata kunci: Motivasi belajar, Kemampuan Pedagogik, Prestasi belajar